第一种,用x-1-代替式中右边的x就可以求出 即f(x)=3(x-1)^2+1
第二种,右边因式分解出带x+1的项,把他用x代替即可
f(x+1)=3x²+6x+3-6x-2
=3(x²+2x+1)-6x-2
=3(x+1)²-6x-6+4
=3(x+1)²-6(x+1)+4
∴f(x)=3x²-6x+4
望采纳谢谢
一般两种方法
令t=x+1 x=t-1
f(t)=3*(t-1)^2+1
f(x)=3*(x-1)^2+1
f(x+1)=3x^2+1
=3*(x+1)^2-6x-3+1
=3*(x+1)^2-6*(x+1)+6-3+1
=3(x+1)²-6(x+1)+4
整体代换 有
f(x)=3*x^2-6x+4
用配方法:
f(x+1)=3x^2+1
=3(x+1)^2-6x-3+1
=3(x+1)^2-6(x+1)+4
所以
f(x)=3x^2-6x+4
令a=x+1
则f(a)=3(a-1)²+1
=3a²-6a+4
即f(x) =3x²-6x+4
f(x+1)=3(x+1)²+1
=3x²+6x+3-6x-2
=3(x²+2x+1)-6x-2
=3(x+1)²-6x-6+4
=3(x+1)²-6(x+1)+4
∴f(x)=3x²-6x+4